LncRNA DNAJC3-AS1 Regulates Fatty Acid Synthase via the EGFR Pathway to Promote the Progression of Colorectal Cancer - Tang, Yanyan; Tang, Rui; Tang, Mengtian; Huang, Ping; Liao, Zhiqiang; Zhou, Jumei; Zhou, Lianqing; Su, Min; Chen, Pan; Jiang, Jiarui; Hu, Yingbin; Zhou, Yujuan; et al. (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common cancers worldwide. Recent studies have shown that long non-coding RNAs (lncRNAs) are involved in tumorigenesis and the development of CRC. By constructing a differential lncRNA expression profile, we screened gene chips and found that DNAJC3-AS1 was highly expressed in CRC tissues and was associated with poor prognosis in patients with CRC. Further, we proved through assays such as wound healing, colony formation, and Cell Counting Kit-8 (CCK8) that interfering with DNAJC3-AS1 could reduce the proliferation, migration, and invasion of CRC cells. Mechanically, we found that DNAJC3-AS1 regulates fatty acid synthase to promote the progression of CRC via the epidermal growth factor receptor/phosphatidylinositol 3-kinase/protein kinase B/nuclear factor κB signaling pathway. Therefore, DNAJC3-AS1 may be a new target for the diagnosis and therapy of CRC.